Molecular physiology of tick salivary secretion and transcriptomics of tick in interaction with tick-borne pathogen - Kim, Donghun (Kansas State University, 2016)
Tick salivary secretion is crucial for survival and for successful feeding. Tick saliva includes excretory water/ions and bioactive components for compromising the hosts' immune responses, and provides a direct route for pathogen transmission. Control of the tick salivation involves autocrine/paracrine dopamine, the most potent stimulator of tick salivation. Our research group reported the presence of two dopamine receptors in the salivary glands of the blacklegged tick (Ixodes scapularis): dopamine receptor (D1) and invertebrate specific D1-like dopamine receptor (InvD1L). Dopamine-induced salivary secretion was orchestrated by two distinct physiological roles via activation of the two dopamine receptors (Chapter 2). Low concentration of dopamine activated D1 receptor on epithelial cells of salivary gland acini leading inward fluid transport. High concentration of dopamine activated InvD1L receptors on axonal projections innervating myoepithelial cells modulating pumping/gating actions for emptying luminal saliva into the main duct. Thus, ticks coordinated salivary secretion with duo dopamine receptors. Dopamine-mediated saliva production involves an important downstream component, Na/K-ATPase (Chapter 3). Na/K-ATPase was found in the epithelial cells of all types of acini. However, Na/K-ATPase had two different functions in salivary secretion in different acini: 1) dopamine-mediated production of primary saliva in distally located salivary gland acini type-2/- 3, and 2) dopamine-independent resorption in proximally located salivary gland acini type-1. Type-1 acini were also found to function in direct water absorption of off-host ticks, which could be a potential route for delivery of acaricides. Chapter 4 investigated the comparative transcriptomics of the lone star tick underlying the processes of pathogen acquisition. Differential expression analyses in pathogen-exposed ticks revealed a number of transcripts that are important in the tick-pathogen interaction. These included genes for tick immunity against pathogen and for modulation of tick physiology facilitating a pathogen’s invasion and proliferation. My study expanded the understanding of physiological mechanisms controlling tick salivation. In addition, transcriptomics of ticks in interaction with pathogen identified several genes that are relevant in vector/pathogen interactions. The knowledge obtained in my study will facilitate to the development of novel methods for the disruption of tick feeding and pathogen transmission.
Keywords: Na/K-ATPase; GPCRs; Salivary glands; Transcriptomics; Dopamine receptor